Where would you turn for help? Older adults' awareness of community health and support services for dementia care - Margaret Denton; Jenny Ploeg; Joseph Tindale; Brian Hutchison; Kevin Brazil; Noori Akhtar-Danesh; Monica Quinlan; Jean Lillie; Jennifer Millen Plenderleith; Linda Boos (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2010)
Previous findings on older adults' awareness of community support services (CSSs) have been inconsistent and marred by acquiescence or over-claiming bias. To address this issue, this study used a series of 12 vignettes to describe common situations faced by older adults for which CSSs might be appropriate. In telephone interviews, 1,152 adults aged 50 years and over were read a series of vignettes and asked if they were able to identify a community organization or agency that they may turn to in that situation. They were also asked about their most important sources of information about CSSs. The findings show that, using a vignette methodology, awareness of CSSs is much lower than previously thought. The most important sources of information about CSSs included information and referral sources, the telephone book, doctors' offices, and word of mouth.
Keywords: I18; 330; aging; community support services; awareness; knowledge; acquiescence bias; vignette methodology; Alte Menschen; Alterskrankheit; Gesundheitsversorgung; Kanada